Assessment of semi-active friction dampers in auxiliary mass dampers' suspension. (1st May 2019) - dos Santos, Marcelo Braga; Coelho, Humberto Tronconi
Highlights: A semi-active friction damper was used to tune an auxiliary mass system. Semi-active friction dampers eliminate the resonant peaks of the vibratory structure. The proposed device is efficient to reduce the vibration of N-DOF systems. The proposed tunable auxiliary mass damper proved to be an efficient energy sink. The proposed device allows 50% mass reduction compared with similar devices. Abstract: Because of the efficiency of semi-active friction dampers to dissipate mechanical energy, their use have been extensively proposed for a variety of mechanical systems to reduce vibration amplitudes. A considerably simple model for a semi-active friction damper can be obtained with the use of an elastic element coupled to a vibratory system through a variable friction joint. Another approach against excessive vibrations in mechanical structures is the addition of auxiliary mass systems by means of elastic elements and viscous dampers—the auxiliary mass damper (AMD). However, their performance is susceptible to changes in the frequency or form of the excitation force. Therefore, to improve their robustness, it is necessary to design adaptive systems, i.e., adjustable devices that can be used efficiently over a large frequency range. In this work, a semi-active friction damper was used in the auxiliary mass damper's suspension to tune it by altering the normal force in the friction joint while it dissipates the mechanical energy from the primary vibratory structure. This AMD was named tunable auxiliary mass damper. Furthermore, assemblies using semi-active friction dampers and tunable auxiliary mass dampers were numerically simulated in order to evaluate their effectiveness in the vibration attenuation. Numerical experiments in a multiple-degree-of-freedom vibratory structure were performed and efficiencies of the proposed assemblies were evaluated by means of a performance parameter obtained from their frequency responses. Moreover, their robustness was assessed by imposing several types of excitation forces. Numerical responses that use seismic records as base excitations were obtained for comparison with results in the literature through performance indexes normally used for seismic damage prevention studies. The obtained results presented a promising performance for the selected assemblies that use different positions for friction devices.